Analisis Pengaruh Sumber Daya Manusia terhadap Kualitas Laporan Keuangan Pada Kantor Kelurahan Sukajaya Kota Palembang - Andini Utari Putri; Vhika Meiriasari; Puspa Djuita (Universitas Indo Global Mandiri)
Human resources play an important role in the quality of financial reports. With human resources (HR) who are competent and have a high understanding of managing regional finances, it will also improve the financial reporting they report or which will be presented in accordance with the characteristics of financial statements. The Sukajaya Sub-District Office, several staff who helps in the finance department also has an educational background of high school graduates. This study aims to analyze the influence of human resources on the quality of financial reports at the Sukajaya Village Office, Palembang City. This study uses secondary data in the form of observations (observations). The results showed that the Sukajaya Village Office already had human resources in accordance with the field assigned, namely the financial sector, although not all parties had an undergraduate education background, namely a minimum of high school. Human Resource Competence is the ability of an employee related to knowledge, skills, and attitudes in completing their performance so that they can achieve the desired goals. The Sukajaya Sub-District Office, Palembang City should provide training to staff related to the financial sector so that later they are able to carry out functions related to the financial sector. Keywords: Human Resources, Quality of Financial Reports